KEEFEKTIFAN MODEL MIND MAPPING BERBANTU MEDIA AUDIOVISUAL PADA MATA PELAJARAN IPA TERHADAP HASIL BELAJAR SISWA KELAS IV SD NEGERI JRAGUNG 3 DEMAK - Saputra, Randy Dwi; Saptaningrum, Ernawati; Listyarini, Ikha (JGK (Jurnal Guru Kita), 2019)
Abstract: The Effectiveness of Mind Mapping Models Assisted by Audivisual Media in Natural Sciences Subjects on Learning Outcomes of Grade IV Students of SDN Jragung 3 Demak. This study aims to determine whether the mind mapping learning model assisted by audiovisual media is effective against the learning outcomes of Natural Sciences subject class IV SD Negeri Jragung 3 Demak.This type of research is quantitative with pre-experimental design research methods with one-group pretest-posttest design. Data in this study were obtained through interviews, documentation, and tests.The results of the analysis of the initial normality test data (pretest) L0 0.1216